Efektivitas Lama Perendaman Benih Padi dalam Kultur Mikroorganisme Lokal (MOL) Bonggol Pisang Terhadap Pertumbuhan dan Produksi Padi - Argadatta Sigit; Rosdiana; Dameria (LPPM Universitas Terbuka, 2023)
The need for rice from year to year continues to increase due to the growing population of Indonesia, but this is not balanced with sufficient rice production. This is what makes it difficult for Indonesia to be self-sufficient in food so that efforts are needed to increase rice production nationally so that domestic rice needs are met. This panel aims to see the effectiveness of long soaking of rice seeds in MOL banana weevil on vegetative growth and yield of Ciherang variety rice plants. The research was conducted in November 2021 – March 2022 on open land of BPP Caringin, Legok District, Tangerang Regency. The study was conducted using the Randomized Complete Group Design (RKLT) method consisting of 5 treatments, namely control (without soaking MOL banana weevil), soaking rice seeds for 6 hours, 12 hours, 18 hours, and soaking for 24 hours. Each treatment was repeated 5 times so that there were 25 experimental units. Each experimental unit consists of three plants, the number of plants to be studied is 75 plants. Soaking seeds in MOL banana weevil for 24 hours gives the best results for the growth and production of Ciherang rice plants.